KINERJA RELAY JARAK DI TRANSMISI BERDASARKAN PENGARUH STATCOM - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
By using equipment FACTS (flexible AC transmission systems) on the transmission line is an attempt to make the Electric Power System more efficient and reliable is one compensation equipment in FACTS is STATCOM or static synchronous compensator. Controlling the voltage stability on the transmission line can use Static synchronous compensator, so as ultimately increase the power transfer capability on the channel. Voltage and current signals in the relay will be affected by the STATCOM on the transmission line. This influence would have no effect on the performance of the protection system, such as the distance relay. This research will discuss about the transmission line is compensated by STATCOM based on the performance of the distance relay.